343 Sending citizen responders to private apartments is safe and necessary. (1st May 2022) - Bender, M; Ewering, L; Poloczek, S; Pommerenke, C; Stiepak, J
Abstract : Background: Alerting citizen responders to Out-of-Hospital-Cardiac Arrest (OHCA) increases the rate of bystander-CPR and improves neurological outcome. There is an ongoing discussion, whether to send lay responders to cardiac arrest calls in patients' residences. The smartphone-based dispatch systems for citizen responders in Berlin (KATRETTER) includes activation of citizen responders to all OHCA with only a few exceptions. This study aims to analyze demographics and acceptance of citizen responders entering private appartements and safety for both first responders and patients. Method: Retrospective analysis of the data from the smartphone-based dispatch system for citizen responder „KATRETTER' and prehospital outcome data from the Berlin EMS including all OHCA-alarms to which a citizen responder was alerted in the period from 28.09.2020 and 28.02.2021. Results citizen responders were activated to suspected OHCA 4614 times, of these 2305 (=50%) were located in private apartments. Citizen responders arrived on scene at residential locations 1053 times (=45, 7%) and prior to EMS in 628 cases (27, 3%). There was a significant difference in confirmed OHCA and CPR-attempts between the residential setting (38, 9%) and calls in public spaces (14, 5%). In 11 cases (1%) citizen responders were not granted access to the private apartment. During the observation period there were no reports of any legal or ethical problems. Conclusion: Sending citizens responders to these calls is safe and even necessary, as most of the OHCA occurred in private apartments. Also the absolute number and the ratio of suspected to confirmed OHCA is higher in the residential setting than in public. Conflict of interest: None declared. Funding: None declared.